Left-Behind Children’s Well-being: A Systematic Review of Parental Migration Impacts - Alfiasari, Alfiasari; Wahyuni, Ekawati Sri; Sumarti, Titik; Kolopaking, Lala M. (Journal of Family Sciences, 2025)
This systematic review synthesizes evidence from 23 peer-reviewed studies to examine the multidimensional impacts of parental migration on the well-being of left-behind children (LBC). Given the rising global trends in labor migration, understanding its implications on child well-being is crucial for determining child protection frameworks. This review adopted the PRISMA included over 80,000 child participants from studies conducted across Asia, Eastern Europe, and Sub-Saharan Africa. It identified five core domains of child well-being affected by parental absence: psychological-emotional health, social-relational functioning, educational outcomes, physical health, and subjective well-being. Maternal migration, inconsistent caregiving, and weak parent-child communication were consistently associated with poorer emotional security and academic performance outcomes. In contrast, stable caregiving by educated guardians and sustained emotional contact with migrant parents mitigated some negative effects. Mediating factors, such as caregiver quality, peer and school support, and gender dynamics, influenced how children internalize the migration experience. These findings consistently highlighted that the nature and quality of caregiving environments are critical in mediating the developmental risks associated with parental migration. This review underscores the urgent need for migration and welfare policies prioritizing family unity and children’s voices in decision-making.